Comparative Study of Bukhur and Hio in Interfaith Dialogue - Ilham Ramadhan Daulay; Elly Warnisyah Harahap (International Journal of Multidisciplinary Research of Higher Education, 2026)
Ritual aroma represents a sensory dimension in religious practice that bridges symbolism, spirituality, and cultural identity. This study examines the comparative use of Bukhur in Islam and Hio in Confucianism, both employing fragrance and smoke yet grounded in distinct theological foundations, ritual functions, and symbolic meanings. The research aims to analyze similarities and differences in their theological basis, ritual position, symbolic interpretation, and relevance to interfaith dialogue in Indonesia. Using a qualitative descriptive method with comparative and theological approaches, data were collected through literature review of religious texts, hadith compilations, Confucian teachings, and relevant scholarly studies. Findings reveal that Bukhur in Islam functions primarily as fragrance supporting cleanliness, comfort, and devotion, permitted or recommended as long as it avoids associations with superstition or claims of mystical power. Conversely, Hio in Confucianism holds a formal role in worship, symbolizing sincerity, reverence, and harmonious relations among Tian, humanity, ancestors, and the cosmos through ritual order (Li). This research highlights that contextual understanding of ritual symbols fosters interreligious literacy, reduces misinterpretation, and strengthens tolerance within Indonesian society, thereby contributing to constructive interfaith engagement.